Design Model for Empowering Partner Farmers of PT SBI through Design Thinking Approach and Triple Layered BMC - Muhamad Saeful Azis; Fadia Dewanda; Debby Nadya Asti; Yulya Handayani (Journal of Technopreneurship on Economics and Business Review, 2023)
The purpose of this study is to design an empowerment model for shallot farmers who are partners of PT SBI in Brebes Regency to improve their welfare through a mentoring unit as part of PT SBI. The empowerment model was designed using a design thinking approach. First, an Empathy process was conducted through interviews with farmer representatives and a Focus Group Discussion with PT SBI management to map stakeholders and identify the problems. In the Define process, the main problems were concluded: farmer's capital, standardization of shallot production and market development. The idea process was carried out using the Triple-Layered Business Model Canvas (TLBMC) to design a mentoring unit model on the economic, social, and environmental layers. The result of this study is a prototype of the shallot farmer empowerment model through a mentoring unit at PT SBI.